Application of vascularized fibular graft for reconstruction and stabilization of multilevel cervical tuberculosis: A case report. Issue 3 (January 2018) - Zhang, Jian; He, Wen-Si; Wang, Cheng; Yan, Yi-Guo; Ouyang, Zhi-Hua; Xue, Jing-bo; Li, Xue-Lin; Wang, Wen-Jun
Abstract : Abstract: Multilevel cervical reconstruction and fusion after cervical tuberculosis has always been a challenge. The current implantation materials for cervical fusion, including titanium mesh, cage, and plate are limited by its inferior biological mechanical characteristics and the properties of the metallic material. This has led to the increased risk of recurrent infection after surgery. In addition, the unique nature of tuberculosis infection results in the low rate of cervical fusion and high risk of recurrence. This case report presents 1 patient who suffered from long segmental cervical tuberculosis and had reconstruction surgery using a vascularized fibula graft. The patient had successful graft incorporation 3 months postsurgery and was followed-up for 30 months. In this review, we detail the advantages of using vascularized fibular grafts and compare it with other types of grafts.